Evaluating the E-Office Policy in the Corporate Secretary Department of PT Agrinas Jaladri Nusantara (Persero): A Public Policy Implementation and Evaluation Perspective - Restu Prayogi; Kristyan Dwijosusilo; Kresna Adhi Prahmana (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study evaluates the implementation of the E-Office policy within the Corporate Secretary Department of PT Agrinas Jaladri Nusantara (Persero), an Indonesian state-owned enterprise that recently diversified its core business. While digital administration is widely promoted to improve public-sector effectiveness, many initiatives stall at the implementation stage. Framed by George C. Edwards III’s implementation model (communication, resources, disposition, and bureaucratic structure) and William N. Dunn’s policy-evaluation criteria (effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness), the research asks how the E-Office workflow operates, how the system supports administrative management, and how ready the staff are to operate it. A descriptive-qualitative case-study design was used; data were gathered through observation, in-depth interviews with four key informants selected purposively, and document analysis, then examined using the Miles, Huberman, and Saldana interactive model and source triangulation. The findings show that E-Office accelerates correspondence, increases transparency through digital trails, and eases document tracking, yet its appropriateness and equity remain limited by tiered-approval bottlenecks, technical instability, off-system drafting, rigid letter-numbering rules, under-used features, and uneven staff competence after organisational restructuring. The study concludes that the success of an E-Office policy is not determined by the technology alone but by the interaction among system design, organisational structure, and user behaviour, requiring continuous communication, capacity building, and policy-instrument updates.